2019
DOI: 10.1029/2019jc015289
|View full text |Cite
|
Sign up to set email alerts
|

The Malvinas Current at the Confluence With the Brazil Current: Inferences From 25 Years of Mercator Ocean Reanalysis

Abstract: Twenty‐five years of high‐resolution (1/12°) ocean reanalysis are used to examine the Confluence of the Malvinas Current (MC) with the Brazil Current (BC) from synoptic to interannual time scales. The model transports of the MC (38.0 Sv ± 7.4 Sv 57 at 41°S) and the BC (23.0 Sv ± 11 Sv at 36°S) agree with observations. The model shows the branching of the MC near the Confluence with an offshore branch returning south and an inner branch sinking below the BC and managing to continue northward along the continent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 51 publications
(102 reference statements)
8
66
0
Order By: Relevance
“…The resilience capacity of the benthic communities dependent on SBF productivity is also a key issue which requires further investigation. Stronger warming trends in subsurface waters reported by our study (Figure 8) are consistent with observations from Artana et al (2019), who report a long-term trend of BC intensification and warming at 36 • S in the upper 1,000 m (see their Figures 13A,C). The southward displacement of the tropical BC waters and the induced changes in the advection of BC deeper waters are suggested to induce such changes in the warming trend of deeper waters (their Figures 2, 13).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The resilience capacity of the benthic communities dependent on SBF productivity is also a key issue which requires further investigation. Stronger warming trends in subsurface waters reported by our study (Figure 8) are consistent with observations from Artana et al (2019), who report a long-term trend of BC intensification and warming at 36 • S in the upper 1,000 m (see their Figures 13A,C). The southward displacement of the tropical BC waters and the induced changes in the advection of BC deeper waters are suggested to induce such changes in the warming trend of deeper waters (their Figures 2, 13).…”
Section: Discussionsupporting
confidence: 93%
“…The model assimilates observations with a 7−day assimilation cycle (Lellouche et al, 2013), including along−track satellite altimetry data from CMEMS (Pujol et al, 2016), satellite SST from NOAA, sea−ice concentration, and in situ temperature and salinity vertical profiles from the latest CORA in situ databases (Szekeley et al, 2016). GLORYS12 provides a realistic representation of the general circulation of the SWAO and the location of the BMC (Artana et al, 2018(Artana et al, , 2019.…”
Section: Glorys12 Datamentioning
confidence: 99%
“…Extreme transport maxima in the MC at 41°S were related with cyclonic eddies detached from the PF that propagate northward along the 400‐m isobath (Artana et al., 2018a). The significant energetic peaks in a 30–110‐day period band found in the MC transport at 41°S and in the velocity time series associated with the subducted inner branch of the MC at 37°S (Artana et al., 2019) could be associated with TW. Theoretical works also suggested that TW could affect the position of the encounter of the Brazil and Malvinas Current (Lebedev & Nof, 1997).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…High‐resolution ocean models (1/12°) that assimilate in situ observations and along‐track satellite altimetry, such as the Mercator Ocean physical reanalysis at 1/12°, could provide some insights on TW propagating along the Patagonian shelf break. Previous works have assessed the performance of this reanalysis in the MC system (Artana et al., 2018a, 2019). Here, we further evaluate the spectral content of the reanalysis SLAs and velocities on the slope compared to observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation